Diskursus Akad Pembiayaan Bank Syariah dalam Perspektif Hukum di Indonesia - Hana, Kharis Fadlullah; Dimam, Islahud (Sharia Faculty Islamic Economic Law Study Department, 2022)
This research focuses on the process of forming Islamic bank financing contracts in general. Which distinguishes between two sorts of deeds: genuine deed and private deed. In addition, the search for information on how the OJK product standards are used in financing contracts, as well as the requirements of the Indonesian law that governs the drafting of the deed, which contains sections of the whole deed. In addition, the researchers made modifications based on the data acquired and provided and detailed how to make and prepare a good and accurate act that was suitable based on Indonesian legal requirements. A explanation of how the form of correctness and duty of a notary in making the contract was also included by the researcher. The inclusion of components that constitute the foundation of sharia principles taken from the Qur'an and Hadith at the commencement of the deed would weaken the legitimacy of the deed and will receive sanctions, specifically the deed will be degraded into a deed under hand, according to this research. Then there are the findings of many infractions that may face similar consequences in the future.